(untitled) (Research, Society and Development, 2020)
Currently, in order to increase the supply of products for celiacs, new raw materials have been added in the biscuit formulations. Therefore, buriti flour (BF) is a viable alternative for the preparation of these products. The study aimed to prepare gluten-free cookies containing BF. For that, four formulations were produced containing 0%, 2.5%; 5.0% and 7.5% BF. The analysis of technological characteristics, color and sensory evaluation were performed. The BF provided higher (p<0.05) weight losses and the concentration of 7.5% provided a higher (p<0.05) spread ratio in the cookies. For the color, the lightness was lower with 7.5% BF. The chroma increased from the concentration with 5.0% BF, indicating an increase in the intensity of the orange color. Hue values decreased with the BF addition. The total color difference increased with 2.5 and 5.0% BF, followed by 7.5% BF. The BF addition generally provided cookies with good sensory acceptance. The formulation containing 5.0% was the one that stood out with greater acceptance compared to the others. The CATA analysis indicated that greater acceptance was associated with the terms "pleasant color", "tasty", "sweet taste" and "rice flour flavor", which presented more frequently for control formulations, with 2.5% and 5.0% BF. Cookies with 7.5% BF had the lowest acceptance, indicating that the level of 5.0% is the most suitable for the preparation of cookies.